From Perspectives of the Elderly: Quality of care in Germany - Woods, Dorian R. (Journal of Tourism, Sustainability and Well-being, 2014)
This article reviews state-of-the-art findings on care and quality from published research from 2003-2014 in Germany, specifically from the perspective of the elderly. It is based on a larger project on care and quality in Germany that was funded by the Hans Böckler Foundation. The study provides a much needed overview of current issues on quality and care in light of increased pressure to address care and changes in German social policy. Although quality also encompasses conditions for professional care work and informal carers, this article focuses on the elderly as recipients of care, their perspectives and the ways in which they are involved in their care. Research on care quality from the perspective of the elderly is highlighted in the following themes: 1) the rights of the elderly to quality care 2) elderly perception of satisfaction and quality of outcomes of care, 3) documentation of care as quality control and time, 4) active aging and 5) equality of access. Results show that long-term care rights are more clearly defined and expanded, but enforcement problems are present. Satisfaction with care is traced to good communication with carers, but time for care is scarce. Active aging has become a central focus of care and more research on equal access is needed. The article outlines strengths and weaknesses in German quality care provision as well as learning effects for other countries.